Inhibition of cardiac pacemaker channel hHCN2 depends on intercalation of lipopolysaccharide into channel‐containing membrane microdomains. (7th February 2014) - Klöckner, Udo; Rueckschloss, Uwe; Grossmann, Claudia; Matzat, Saskia; Schumann, Katja; Ebelt, Henning; Müller‐Werdan, Ursula; Loppnow, Harald; Werdan, Karl; Gekle, Michael
Abstract : Key points: The regulation of cardiac function is seriously impaired in severe inflammatory diseases. One characteristic of this dysfunction is a strong reduction in heart rate variability (HRV) so that the cardiac cycle is more regular. This phenomenon is strongly correlated with an unfavourable prognosis in patients with systemic inflammation. Although the depression in HRV can be partially explained by the interplay between cardiac pacemaker channels and lipopolysaccharide (LPS) liberated from the outer walls of Gram‐negative bacteria, the underlying mechanism is still elusive. Using HEK293 cells stably expressing a cardiac pacemaker channel, we demonstrate that only intact LPS molecules can intercalate into target cell membranes and then directly interact with extracellular parts of pacemaker channels. Intracellular signalling cascades do not contribute to LPS‐dependent channel modulation. The present results help to elucidate how LPS interacts with pacemaker channels to attenuate the regularity of the cardiac cycle. Abstract: Depressed heart rate variability in severe inflammatory diseases can be partially explained by the lipopolysaccharide (LPS)‐dependent modulation of cardiac pacemaker channels. Recently, we showed that LPS inhibits pacemaker current in sinoatrial node cells and in HEK293 cells expressing cloned pacemaker channels, respectively. The present study was designed to verify whether this inhibition involves LPS‐dependent intracellular signalling and to identify structures of LPS responsible for pacemaker current modulation. We examined the effect of LPS on the activity of human hyperpolarization‐activated cyclic nucleotide‐gated channel 2 (hHCN2) stably expressed in HEK293 cells. In whole‐cell recordings, bath application of LPS decreased pacemaker current ( I hHCN2 ) amplitude. The same protocol had no effect on channel activity in cell‐attached patch recordings, in which channels are protected from the LPS‐containing bath solution. This demonstrates that LPS must interact directly with or close to the channel protein. After cleavage of LPS into lipid A and the polysaccharide chain, neither of them alone impaired I hHCN2, which suggests that modulation of channel activity critically depends on the integrity of the entire LPS molecule. We furthermore showed that β‐cyclodextrin interfered with LPS‐dependent channel modulation predominantly via scavenging of lipid A, thereby abrogating the capability of LPS to intercalate into target cell membranes. We conclude that LPS impairs I hHCN2 by a local mechanism that is restricted to the vicinity of the channels. Furthermore, intercalation of lipid A into target cell membranes is a prerequisite for the inhibition that is suggested to depend on the direct interaction of the LPS polysaccharide chain with cardiac pacemaker channels.